Accreditation visit, 3 May 2023: UiTM Kota Samarahan, Sarawak / Nur Atiqah Husaini ... [et al.] - Husaini, Nur Atiqah; Hamzah, Hanisah Aimi; Abdul Rahman, Abdul Ruqaim Ashraff; Aziz, Syazwani Aqmar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
On 23rd May 2023, an accreditation visit by Masjlis Akreditasi Pendidikan Senibins (MAPSM) was held in UiTM , Kota Samarahan. This session was attended by the MAPSM representative Dato’ Ar. Dr. Ku Azhar Ku Hassan and Dr. Kamarul Afizi Kosman, as well as the faculty’s PNC, Professor TPr. Dr. Jamalunlaili Abdullah, KP Senibina dan Senibina Dalaman, Dr. Hailane Salam and Trek HEA&A, Prof Madya Ts. ChM. Dr. Mohamad Isa Mohamadin. Selected students’ works was displayed at the Architecture Gallery located at Pusat Pelajar, UiTM Kota Samarahan. A huge appreciation to KPP SSSPU, Sr. Dr. Asmah Alia Mohamad Bohari who has helped with the accreditation visit and all student members of AZV that has helped with the event